UNDERSTANDING THE DYNAMICS OF CORN MARKET INTEGRATION IN EAST JAVA - Lestari, Hasti Wuri; Susilo, Achmadi; Wisnujati, Nugrahini Susantinah (PROCURATIO: Jurnal Manajemen & Bisnis, 2024)
This study aims to analyze price variations at both the producer and consumer levels (1), investigate price transmission elasticity (2), and assess the degree of integration in the vertical corn market between producers (farmers) and consumers (retailers) in East Java Province (3). The analysis of market integration serves as vital input for the government in formulating agricultural development policies within the research area. Conducted as a quantitative study, this research utilized secondary data, specifically monthly time series data spanning from January 2018 to December 2021. The data included corn price information at the producer level sourced from the Agriculture and Food Security Office of East Java Province, and consumer-level corn price data obtained from the East Java Province Industry and Trade Office (SiSKAPERBAPO website). The data underwent descriptive quantitative analysis. The findings reveal that the coefficient of price variation at the producer level is 8.9 percent, indicating high fluctuation and instability, whereas at the consumer level, it stands at 2.8 percent, signifying lower and stable fluctuations. The price elasticity (et) of corn for the years 2019-2021 was calculated as 0.0033 (inelastic), -0.2029 (inelastic), and 2.6359 (elastic), respectively. These results suggest that the rate of price change at the consumer level exceeded that at the producer level (an et value > 1 indicates inefficient corn marketing). The analysis of corn market integration in East Java reveals weak integration between producer and consumer markets in both the short and long terms. This indicates imperfect transmission of market information by market participants, particularly large traders who play a significant role as price setters.